Analisys Lembak Language Preservation Among Teenagers of The Lembak Tribe Neighbourhood 17 Dusun Besar Subdistrict Bengkulu City - Meilani Putri; Edi Ansyah; Vebbi Andra (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
This study aims to determine the forms of Lembak language maintenance and the factors influencing Lembak language maintenance among teenagers in RT 17, Dusun Besar Village, Bengkulu City. The type of this research is qualitative, while the method used in this research is descriptive. This research uses data collection techniques such as observation, interviews, and documentation. The findings from the observations and interviews conducted can be concluded that the Lembak youth in RT 17, Dusun Besar Village, are familiar with the Lembak language and continue to use it when interacting with parents and family members at home. However, when interacting with peers, many believe that they do not always use the Lembak language because some friends do not understand it. Based on the research findings, the conclusion of this study is: (1) The total number of Lembak tribe members in RT 17, including their descendants, is 47 people from the Lembak tribe. Forms of preserving the Lembak language, (2) The form of language preservation of Lembak among the youth of RT 17 is by introducing the Lembak language from an early age and continuing to use the Lembak language when interacting with parents and family members at home, and the youth also continue to use the Lembak language with friends who are also of Lembak descent. (3) There are four factors in the preservation of the Lembak language in RT 17 based on the research findings, namely the factor of descent, the factor of residence, the factor of loyalty in preserving the native language, and the factor of tolerance present in the community.